Comparative estimation of spring forms of triticale according to some quantitative traits - P. I. Stepochkin; T. S. Bauer (Зерновое хозяйство России)
The study was conducted to estimate and select spring breeding and collection forms of triticale for hybridization based on the calculation of the contribution of quantitative traits to plant ear productivity and to grain nature weight. The material was manually laid in black fallow on the plots of 0.5 m2 in 2021 and 2023. There were studied thirty-two spring triticale samples from the world collection of VIR and 31 breeding forms of wheat-rye amphiploids developed on the basis of hybridization of emmer wheat T.dicoccum (Schrank) Schuebl. with the facultative form of triticale UK30/33 (×Triticosecale Wittmack ex A. Camus) according to a set of quantitative traits that correlate with grain weight per ear and with grain nature weight. The selection of the best forms of wheat-rye amphiploids was carried out using the method of correlation analysis and based on the developed algorithms for calculating the coefficient of significance and the general estimation according to a set of traits. There was considered a contribution of each trait to grain weight per ear and with grain nature weight. According to the calculated high breeding value based on a set of the most important traits of spring triticale, there were selected 10 collection samples of triticale and 10 breeding forms of wheat-rye amphiploids with emmer cytoplasm. Three triticale samples ‘Susi (k-3535)’, ‘Karmen (k-3933)’ and ‘Arsenal (k-3874)’ from the world collection of VIR showed a 44–48-day interphase sprouts-heading period in 2021 and 33–38 days in 2023, more than 3 g of grain weight per ear, more than 46 g of 1000-grain weight. They have been selected as parental forms for hybridization in the breeding program. The breeding forms developed based on emmer crossings with triticale were characterized by a grain nature weight exceeding 700 ml/g. They are going to be used in further breeding.